Optimalisasi sumber informasi ilmiah open access dalam mendukung proses pembelajaran pada masa pandemi Covid-19 di Universitas Bangka Belitung - Kusuma, Arja; Darma, Darma (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2022)
Background. This article explains how the Bangka Belitung University Library optimizes open access scientific information sources in supporting the learning process at Bangka Belitung University during the Covid-19 pandemic. As is known, during the pandemic, it is impossible to access services face-to-face at the library.Methods. The research method used in this research is a descriptive qualitative research method. The instrument in this study was the researcher himself. This research was conducted at Library of Bangka Belitung University, the data in this study were collected with observation techniques and documentation related to the optimization of open access scientific information sources in support of the learning process at Bangka Belitung University.Results and discussion. Optimizing the use of open access scientific information sources can be done by, firstly making selected information services from open access scientific information sources, secondly providing search assistance services and downloading electronic books and journals, thirdly through socialization through webinars, social media and user education.Conclusions. The many and varied sources of open access scientific information can be optimized for use in supporting the learning process at Bangka Belitung University, especially during the COVID-19 pandemic